Solar radiation estimation on a tilted surface using sky models in the Afar region of Ethiopia - Alemu, Anshebo Getachew; Anshebo, Teketel Alemu; Dessie, Bizuayehu Bogale (Frontiers in Energy Research, 2025)
The aim of this study is to estimate solar radiation on an inclined surface using sky models. Two anisotropic (direction dependent) and two isotropic (independent of direction) sky models were used for 12.11°N (latitude) and 40.63°E (longitude) in the Afar region of Ethiopia. The sky model outputs were compared to sample statistical test data from the Ethiopian Meteorological Institute and found to exceed expectations in all cases. We found that the Hay and Davies model predicted the highest incident solar radiation throughout the year. Finally, the model that we propose for estimation of solar radiation events on a tilted surface is the Liu and Jordan (LJ) isotropic model, which has the fewest statistical errors out of all the models evaluated in this study and shows good agreement with the estimated data.